PEMANFAATAN SIMULATOR SIMULIDE SEBAGAI SIMULASI RANGKAIAN MESH 2 LOOP DISERTAI PEMBUKTIAN DENGAN PRAKTIKUM REAL - Hana Maulida Fitriah; Syifaul Fuada; Inda Ahmayani; Nurul Syahira Amril; Zahara Murni; Nusaibah Fathul Jannah (UNIVERSITAS PGRI MADIUN, 2023)
SimulIDE is an open-source simulator that can be used offline to support electronic learning because it is designed to help users simulate electronic circuits virtually. This research is intended to test the performance of the SimulIDE simulator by conducting a comparative study of a mesh 2-loop circuit with a comparison of real practicum, simulator test results, and manual calculations. SimulIDE, which is a new simulator, certainly has limitations. However, SimulIDE, an easy-to-use virtual simulator, can be an alternative to simulating and studying electronic circuits. The benefits that can be obtained are knowing the two-loop mesh circuit assembled through the SimulIDE virtual simulator and the real circuit and comparing the amount of voltage obtained from the results of manual calculations, simulator calculations, and real calculations.